Effectiveness of Nominal and Interacting Group Decision Processes for Integrating R&D and Marketing - Souder, William E. (Management Science, 1977)
Because R&D and marketing are dependent upon each other for new product development, it is imperative that they achieve consensus and organizational integration (a team spirit of collaboration and joint commitment). But, consensus and integration are often inhibited by the differing viewpoints of R&D and marketing, which are a natural consequence of their specialized organizational roles and cultures. There is a need for a process that will bridge these dissonant viewpoints and cultures, while otherwise preserving the specialized orientations of the two parties. The bridging properties of three group decision making processes—nominal, interacting, and combined nominal-interacting—were tested by nine strategic planning teams, each composed of R&D and marketing personnel. The combined nominal-interacting process yielded very high levels of statistical consensus and group integration. The nominal process produced statistical consensus but it did not yield high levels of integration. The interacting process did not produce either consensus or integration. The results here and elsewhere indicate that consensus and collaboration problems between R&D and marketing may be alleviated by replacing the interacting decision making process, which is typically used by many organizations, with a combined nominal-interacting process.